Aspects and Influence of Social Media Marketing in Today’s World: A Review of Scholarly Articles - Dr. Sourabh Bhattacharya; Prof. Arpita Majumdar (International Journal of Engineering and Management Research, 2020)
Social media has carried out a lot of value additions for different stakeholders in today’s world. However, comprehensive literature reviews on different aspects of social media marketing are quite a few. Also, researchers working in this burgeoning area are eager to know the opinion of past researchers. For this article, a systematic literature review of scholarly articles, related to social media marketing, had been done to collect, examine and analyze previous studies related to social media marketing. Overall, the paper has tried to present a holistic viewpoint of experts on social media marketing.